ANALISIS KUALITAS BUKU PELAJARAN IPS SD - Arifin Maksum, Juwita (Perspektif Ilmu Pendidikan, 2016)
Currently, many primary and secondary education textbooks are published and available in the market, but the quality does not meet the studentsâ€™ needs. The Center for Textbook Development, Ministry of Education and Culture should produce textbook models to facilitate learning. This research conducted as from June through November 2015 examined Social Science textbooks for Grade VI Primary School. The research method used was content analysis and the data were collected by check list forms on the evaluation indicators of the textbooks. The result of the research is expected to become information for the appropriateness of textbooks.